An Outside-In Switch in Integrin Signaling Caused by Chemical and Mechanical Signals in Reactive Astrocytes - Pérez, Leonardo A.; Rashid, Aysha; Combs, J. Dale; Schneider, Pascal; Rodríguez, Andrés; Salaita, Khalid; Leyton, Lisette (Frontiers in Cell and Developmental Biology, 2021)
Astrocyte reactivity is associated with poor repair capacity after injury to the brain, where chemical and physical changes occur in the damaged zone. Astrocyte surface proteins, such as integrins, are upregulated, and the release of pro-inflammatory molecules and extracellular matrix (ECM) proteins upon damage generate a stiffer matrix. Integrins play an important role in triggering a reactive phenotype in astrocytes, and we have reported that αVβ3 Integrin binds to the Thy-1(CD90) neuronal glycoprotein, increasing astrocyte contractility and motility. Alternatively, αVβ3 Integrin senses mechanical forces generated by the increased ECM stiffness. Until now, the association between the αVβ3 Integrin mechanoreceptor response in astrocytes and changes in their reactive phenotype is unclear. To study the response to combined chemical and mechanical stress, astrocytes were stimulated with Thy-1-Protein A-coated magnetic beads and exposed to a magnetic field to generate mechanical tension. We evaluated the effect of such stimulation on cell adhesion and contraction. We also assessed traction forces and their effect on spreading area, cell morphology, and integrin surface expression. Mechanical stress accelerated the response of astrocytes to Thy-1 engagement of integrin receptors, resulting in cell adhesion and contraction. Astrocyte contraction then exerted traction forces onto the ECM, inducing faster cell contractility and higher traction forces than Thy-1 alone. Therefore, cell-extrinsic chemical and mechanical signals regulate in an outside-in manner, astrocyte reactivity by inducing integrin upregulation, ligation, and signaling events that promote cell contraction. These changes in turn generate cell-intrinsic signals that increase traction forces exerted onto the ECM (inside-out). This study reveals αVβ3 Integrin mechanoreceptor as a novel target to regulate the harmful effects of reactive astrocytes in neuronal healing.